Charles Tart’s Contributions to Parapsychology: A Scientific Career Sparked by the Cabbage Patch Kid - Radin, Dean (Journal of Anomalous Experience and Cognition, 2023)
In this Festschrift in honor of Charles Tart, I originally intended to focus on how Charley – as his friends call him – influenced the discipline of parapsychology from his entry into the field in the 1960s to the present day. That turned out to be an overly ambitious goal because Charley has made so many influential contributions, and in so many facets of parapsychology, that it is not possible to cover them all without writing a lengthy monograph. So instead, I offer a few words about how Charley influenced my own involvement in the field, then I mention four topics that continue to shape the way I think about and approach the study of psi phenomena, and I finish my tribute with an edited transcript of a delightful chat I had with him in preparation for writing this article.